How Rainforest Conversion to Agricultural Systems in Sumatra (Indonesia) Affects Active Soil Bacterial Communities - Berkelmann, Dirk; Schneider, Dominik; Engelhaupt, Martin; Heinemann, Melanie; Christel, Stephan; Wijayanti, Marini; Meryandini, Anja; Daniel, Rolf (Frontiers in Microbiology, 2018)
Palm oil production in Indonesia increased constantly over the last decades, which led to massive deforestation, especially on Sumatra island. The ongoing conversion of rainforest to agricultural systems results in high biodiversity loss. Here, we present the first RNA-based study on the effects of rainforest transformation to rubber and oil palm plantations in Indonesia for the active soil bacterial communities. For this purpose, bacterial communities of three different converted systems (jungle rubber, rubber plantation and oil palm plantation) were studied in two landscapes with rainforest as reference by RT-PCR amplicon-based analysis of 16S rRNA gene transcripts. Active soil bacterial communities were dominated by Frankiales (Actinobacteria), subgroup 2 of the Acidobacteria and Alphaproteobacteria (mainly Rhizobiales and Rhodospirillales). Community composition differed significantly between the converted land use systems and rainforest reference sites. Alphaproteobacteria decreased significantly in oil palm samples compared to rainforest samples. In contrast, relative abundances of taxa within the Acidobacteria increased. Most important abiotic drivers for shaping soil bacterial communities were pH, calcium concentration, base saturation and C:N ratio. Indicator species analysis showed distinct association patterns for the analyzed land use systems. Nitrogen-fixing taxa including members of Rhizobiales and Rhodospirillales were associated with rainforest soils while nitrifiers and heat-resistant taxa including members of Actinobacteria were associated with oil palm soils. Predicted metabolic profiles revealed that the relative abundances of genes associated with fixation of nitrogen significantly decreased in plantation soils. Furthermore, predicted gene abundances regarding motility, competition or gene transfer ability indicated rainforest conversion-induced changes as well.